VE-Cadherin Is Required for Lymphatic Valve Formation and Maintenance - Ying Yang; Boksik Cha; Zeinab Y. Motawe; R. Sathish Srinivasan; Joshua P. Scallan (Cell Reports, 2019)
Summary: The lymphatic vasculature requires intraluminal valves to maintain forward lymph flow. Lymphatic valves form and are constantly maintained by oscillatory fluid flow throughout life, yet the earliest steps of how lymphatic endothelial cells are able to respond to fluid shear stress remain unknown. Here, we show that the adherens junction protein VE-cadherin is required for the upregulation of valve-specific transcription factors. Conditional deletion of VE-cadherin in vivo prevented valve formation in the embryo and caused postnatal regression of nearly all lymphatic valves in multiple tissues. Since VE-cadherin is known to signal through β-catenin and the VEGFR/AKT pathway, each pathway was probed. Expression of a constitutively active β-catenin mutant or direct pharmacologic activation of AKT in vivo significantly rescued valve regression in the VE-cadherin-deficient lymphatic vessels. In conclusion, VE-cadherin-dependent signaling is required for lymphatic valve formation and maintenance and therapies to augment downstream pathways hold potential to treat lymphedema in patients. : Oscillatory fluid flow increases the expression of nuclear transcription factors that orchestrate lymphatic valve morphogenesis. Yang et al. investigate how signaling events mediated by VE-cadherin at the cell membrane regulate valve development. They find that VE-cadherin is required for β-catenin and AKT signaling that regulate nuclear Prox1 and Foxc2 expression. Keywords: shear stress, mechanotransduction, Akt, β-catenin